1976
DOI: 10.1002/chin.197629187
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: SYNTHESIS AND BIOLOGICAL ACTIVITY OF 3α‐FLUORO‐9,10‐SECOCHOLESTA‐5,7,10(19)‐TRIENE ‐ A FLUORO DERIVATIVE OF VITAMIN D3

Abstract: Durch photochemische und thermische Isomerisierung wird aus dem Fluorcholestadien (I) das fluoranaloge Vitamin D3 (III) hergestellt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The synthesis of 3β-fluoro-3-deoxyvitamin D 3 (35) from 3β-fluorocholesta-5,7-diene (36) via photochemical transformation followed by thermal isomerization was described by Segal et al in 1976 [37]. It was found that 3β-fluoro-3-deoxyvitamin D 3 (35) had an antirachitic effect analogous to VD 3 .…”
Section: -Fluorinated Vd 3 Analoguesmentioning
confidence: 99%
See 1 more Smart Citation
“…The synthesis of 3β-fluoro-3-deoxyvitamin D 3 (35) from 3β-fluorocholesta-5,7-diene (36) via photochemical transformation followed by thermal isomerization was described by Segal et al in 1976 [37]. It was found that 3β-fluoro-3-deoxyvitamin D 3 (35) had an antirachitic effect analogous to VD 3 .…”
Section: -Fluorinated Vd 3 Analoguesmentioning
confidence: 99%
“…It was found that 3β-fluoro-3-deoxyvitamin D 3 (35) had an antirachitic effect analogous to VD 3 . On the other hand, in 1978, Mazur and coworkers designed and synthesized 3β-fluoro-3-deoxy-1α-hydroxyvitamin D 3 (37) to elicit VD 3 activity. The 3β-fluoro group was constructed from (6R)-hydroxy-3,5-cyclovitamin D 3 (38) by treatment with HF (Scheme 14) [38].…”
Section: -Fluorinated Vd 3 Analoguesmentioning
confidence: 99%